CONVERSATIONAL MAXIMS VIOLATIONS IN THE TONIGHT’S SHOW - Deri Anisa Fitri; Agus Triyogo (LP3MKIL, 2026)
This research aims to identify the types of violation of the conversational maxims in The Tonight Show Starring Jimmy Fallon. The method used was descriptive qualitative, with data collection through observation and audiovisual, social media, and digital materials. Data were obtained from five videos of The Tonight Show Starring Jimmy Fallon. The analysis was conducted through the stages of data condensation, data presentation, and drawing and verifying conclusions. The results showed 85 data conversational maxim violations. Violations of the quantity maxim 35 data, followed by violations of the quality maxim 6 data, violations of the relation maxim 18 data, and violations of the manner maxim 26 ​​data. In conclusion, violation of quantity maxim emerged as the most dominant violated maxim, indicating that speakers often provided either insufficient or excessive information during the interactions. These patterns show that variations in the amount and clarity of information are a natural part of spontaneous talk show communication and contribute to the overall flow of the conversation rather than signaling communicative breakdown.